Legal and contractual foundations of intellectual property of design of construction projects - Behsan, Hossein; Shahhosseini, Vahid (International Journal of Engineering and Technology, 2014)
Viable improvement of any complex in micro and macro scales requires producing novel plans and having the complex to make use of innovative technologies and findings. In most developmental projects, the project consultants are responsible for producing plans and for directing the projects towards providing the opportunity to make use of the mentioned facilities. The beneficiaries' interests are considered as one of the issues to be considered while producing and directing plans. The interests of the projects' consultants include material and intellectual property of the plans made. Because some deficits exist in intellectual property law and the period of the legal proceedings is too long, it is possible that when the plan is made within the project consultancy group, other legal and real persons ignore the goals of the project and begin to use the plan just for the progress of their own interests. Emphasizing on the intellectual property of the plans made by the consultants, present regulations, comprehensiveness of the regulations and the necessity of ratification of the appropriate regulations, this essay deals with the intellectual property of the innovative plans. Keywords: Intellectual Property – Consultant – Plans of Developmental Projects - Contracts.